Faktor-Faktor yang mempengaruhi Earnings Persistence - Ferby Claudia; Arya Pradipta (Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this study is to obtain empirical evidence regarding the effect of the independent variables on institutional ownership, sales volatility, managerial ownership, operating cash flows, permanent book tax differences, and temporary book tax differences on the dependent variable, namely earnings persistence. The population used in this study were manufacturing companies that were consistently listed on the Indonesia Stock Exchange (IDX) during the period 2018 to 2020. The sample selection in this study used the purposive sampling method, and the method used to analyze the data was the multiple regression method. . Based on the predetermined sample criteria, the number of companies used as samples in this study were 35 companies. The results of this study indicate that the independent variable, namely sales volatility, has an influence on Earnings Persistence. Meanwhile, the other independent variables, namely institutional ownership, managerial ownership, operating cash flow, permanent book tax differences and temporary book tax differences have no effect on earnings persistence.